Fracturas de tibia por estrés y hallazgos patológicos asociados en reclutas - Coria, Hernán Eduardo; Fedún Rodríguez, Emanuel; García, Daniel; Masaragian, Héctor; Mizdraji, Luciano; Perin, Fernando; Rega, Leonel; Sartorelli, Daniel; Veizaga Velasco, Johann (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2024)
Introduction: Tibial stress fractures are a very common condition in military recruits. Our objective is to demonstrate that stress fractures are associated with other diseases. Materials and Methods: 42 stress fractures in 34 patients were retrospectively evaluated. Every patient had recently joined the Argentine Army and consulted for painful symptoms in the tibia. A clinical and scintigraphic diagnosis of stress fracture was made. Patient data, associated diseases, and risk factors were documented. Inclusion criteria: recent incorporation, same training, age between 16 and 23 years. Trauma, simulators, tumoral pathology, and cases with negative scintigraphy were excluded. Results: We studied 42 stress fractures in 34 patients, 14 were men and 20 were women. The average age was 20 years. There were no significant differences in the number of injuries regarding the affected limb. 64.7% had associated diseases, 73% in women and 27 % in men. Among the women with stress fractures, 80% had associated diseases, compared to 43% for men. Different diseases were found with lower limb varus and valgus imbalances. Varus was the most associated with fractures. Conclusions: A high rate of associated diseases was found in patients with tibial stress fractures with a predominance of lower limb varus imbalances. Associated diseases were more likely to be found in women with stress fractures than in men.